2021
DOI: 10.2337/dbi20-0006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Metabolism and Cell Growth by the ATF/CREB Family of Transcription Factors

Abstract: The liver is a major metabolic organ that regulates the whole-body metabolic homeostasis and controls hepatocyte proliferation and growth. The ATF/CREB family of transcription factors integrates nutritional and growth signals to the regulation of metabolism and cell growth in the liver, and deregulated ATF/CREB family signaling is implicated in the progression of type 2 diabetes, nonalcoholic fatty liver disease, and cancer. This article focuses on the roles of the ATF/CREB family in the regulation of glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 121 publications
1
36
0
Order By: Relevance
“…Recent reports have highlighted that the ATF/CREB family is involved in regulating many aspects of lipid metabolism processes, including regulating critical enzymes and regulators involved in lipogenesis, fatty acid oxidation, and lipoprotein metabolism [ 23 ]. mRNA levels of members of the ATF/CREB family, such as Atf4 and 6 (Activating Transcription Factor 4 and 6) and Crebh (CAMP Responsive Element Binding Protein), show no significant regulation as a result of the MLN4924 treatment in the CD-HFD and 0.1% MCDD NAFLD mouse models ( Suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have highlighted that the ATF/CREB family is involved in regulating many aspects of lipid metabolism processes, including regulating critical enzymes and regulators involved in lipogenesis, fatty acid oxidation, and lipoprotein metabolism [ 23 ]. mRNA levels of members of the ATF/CREB family, such as Atf4 and 6 (Activating Transcription Factor 4 and 6) and Crebh (CAMP Responsive Element Binding Protein), show no significant regulation as a result of the MLN4924 treatment in the CD-HFD and 0.1% MCDD NAFLD mouse models ( Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, lipid homeostasis is regulated by many transcription factors in the liver that are altered in NAFLD [ 39 ]. For example, members of the ATF/CRBEH family have been shown to increase fatty acid oxidation [ 23 ]. Though we have not observed changes at the transcription level in the intermediates of this family, it should be considered that when we treated with MLN4924, we modify proteins post-translationally, and other regulatory mechanisms, such as cell localization and protein stability, might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…These include CBP and p300, which have been implicated in hepatic insulin sensitivity. Under physiological conditions, insulin inhibits gluconeogenesis by selectively disrupting the interaction between CBP/p300 and the cyclic AMP-responsive element-binding protein (CREB), a TF involved in the expression of metabolic and gluconeogenic genes (129). In functional studies, p300 overexpression in mice was reported to cause hepatic steatosis, insulin resistance, and inflammation (27).…”
Section: Histone Acetyltransferases (Hats)mentioning
confidence: 99%
“…Although it is known that production and secretion of OPN is induced in hepatocytes in NASH 21,25 , the mechanism of OPN in mediating the crosstalk beween hepatocytes and HSCs during fibrosis development in NASH remains largerly unknown. CREB/ATF bZIP transcription factor (CREBZF) is rapidly gaining interest as a key regulator in hepatic metabolism and cell growth 26,27 . CREBZF normally functions as a transcriptional inhibitor to regulate gene expression 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…CREB/ATF bZIP transcription factor (CREBZF) is rapidly gaining interest as a key regulator in hepatic metabolism and cell growth 26,27 . CREBZF normally functions as a transcriptional inhibitor to regulate gene expression 27,28 . During refeeding, CREBZF is induced by insulin to inhibit transcription levels of Insig-2a in the hepatocyte, leading to the activation of SREBP-1 and fatty acid synthesis 29 .…”
Section: Introductionmentioning
confidence: 99%